Efektivitas Adat Suku Tolaki (Kalosara), Sebagai Mediasi Penal Terhadap Pelanggaran Lalu Lntas Di Wilayah Hukum Konawe Provinsi Sulawesi Tenggara - Syaiful Arpin (Jayapangus Press, 2019)
Kalosara as a rules for the tolaki peoples costum in law jurisdiction Konawe (South east Sulawesi) this thesis is a part of a field research abaut kalosara, on the facta kalosara is a set of a tools or symbolic custom that if we used can be fungtion as mediator between two parties were disputing the violation of a traffic accident, so the people by the presence tolaki kalosara can be increase the legal awernes to the people to obey on the rule of law itself. The background these research is that kalosara implication the role of to make a peace,in the conflict and every cases is happening. in the konawe district still felt it until now and have a big influence, this custom have same roles as panel mediation against violation of traffic accident. And then it can be seen that society tolaki inveroment in generally still be used as instrument of fostering the rules of law and the social order. This research talking about tolaki custom activity (Kalosara) as panel mediation in the traffic violation. This research has took in Unaaha subdistrict on the district of Konawe (South east Sulawesi) the researchers take a study about traffic accident case to nyonya Hj. Sitti Aminah as a fictim and Ms. Hasrina as offender. This research use descriptif qualitative, after make an analisist in this research. In the end found that effectivines custom in tolaki (kalosara) given a big contribution to the rule of law in the Konawe district. Multy various either govermant birocration, law anforchman and custom tolaki society itself, they say that tolaki custom (Kalosara) is not a disorder but tolaki custom really rolles to aid rule of law, a peace and save, its not to demage the position of law but to help tolaki custom society to grow and make a consolidation in the rule of law. Specially in the Konawe district. This proved by solved same traffic case that death caused through tolaki custom (Kalosara). The problem is (1). Should be the role of kalosara in the tolaki custom be able to be as a rules to help a good law anforcement agency for the tolaki custom. (2). Should be in the traffic case that caused same people death have to continue in court to given forgiviness for the offender. (3) the result in the peaces tolaki custom (Kalosara) just as consideration the judges to make a little punishment and isn’t to stop traffic case.